7-Hydroxylation of warfarin is strongly inhibited by sesamin, but not by episesamin, caffeic and ferulic acids in human hepatic microsomes. (March 2018) - Pilipenko, Nadezhda; Rasmussen, Martin Krøyer; Doran, Olena; Zamaratskaia, Galia
Abstract: Warfarin is a commonly used anticoagulant drug and is a derivate of coumarin. Cytochrome P450 2C9 (CYP2C9) plays the key role in transformation of coumarin and thus, influences determination of warfarin dosage. A number of factors including dietary compounds such as sesamin, caffeic acid and ferulic acids can regulate the activity of CYP2C9. The present study tested the hypothesis that sesamin, episesamin, caffeic acid and ferulic acid decreases the rate of warfarin 7-hydroxylation via inhibition of hepatic CYP2C9. The experiments were conducted on hepatic microsomes from human donors. It was demonstrated that the rate of 7-hydroxylation of warfarin was significantly decreased in the presence of sesamin in the range of concentrations from 5 to 500 nM, and was not affected by episesamin, caffeic acid and ferulic acid in the same range of concentrations. The kinetic analysis indicated non-competitive type of inhibition by sesamin with Ki = 202 ± 18 nM. In conclusion, the results of our in vitro study revealed that sesamin was able to inhibit formation of a major metabolite of warfarin, 7-hydroxywarfarin. The potentially negative consequences of the consumption of high amounts of sesamin-containing food or dietary supplements in warfarin-treated patients need to be further studied.